Combination of HLA OR and DQ molecules determine the susceptibility to Insuline Dependent Diabetes Mellitus in Iraqi patients - AL-Obeidy, Eman sh.; Saeed, Basil N. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Type I diabetes mellitus is an autoimmune disorder characterized by destruction of insuline producing.